Security and privacy challenges of big data adoption: a qualitative study in telecommunication industry - Anawar, Syarulnaziah; Othman, Nur Fadzilah; Selamat, Siti Rahayu; Ayop, Zakiah; Harum, Norharyati; Abdul Rahim, Fiza (International Association of Online Engineering, 2022)
The telecommunication industry is the leading industry in big data trends as this industry has the most capable infrastructure for big data. However, the adoption of big data in telecommunication services also raises important security and privacy challenges due to the high volume, velocity, and variety of big data characteristics. To address the issue, this study shed light on the security and privacy challenges of big data adoption in the telecommunication industry. This study focuses on investigating the security and privacy challenges for data users in telecommunication services from the lens of the TOE framework and examines the mitigation strategies to address the privacy and security challenges. This study is conducted using qualitative methodology. From the perspectives of data users (telecommunication providers), it could be concluded that data management, data privacy, data compliance, and regulatory orchestration challenges are the most pressing concerns in big data adoption. This study offers contributions in presenting a thematic classification of security and privacy challenges and their mitigation strategies for big data adoption in the telecommunication industry. The thematic classification highlights potential gaps for future research in the big data security domain. This study is significant in that it provides empirical evidence for the perspectives of telecommunication data users in addressing privacy and security issues that are related to big data adoption.